Equivalent dynamic model of multilayered structures with imperfect interfaces: Application to a sandwich structured plate with sliding interfaces. (29th September 2022) - Auquier, Nicolas; Ege, Kerem; Gourdon, Emmanuel
Abstract: This works aims to build an equivalent model of multilayered structures with imperfect interfaces for vibro-acoustic modeling and characterization. To take into account imperfections, new interface conditions including constitutive equations, that describe the imperfections, are implemented. Once the displacement field with imperfect interfaces is obtained, the dispersion relation of the structure is derived from the equivalent model. The bending wavenumbers are then used to compute the equivalent flexural rigidity and the damping of the sandwich panel. In this paper, the methodology is applied to a sandwich panel with sliding interfaces. The equivalent parameters are computed and compared to the reference case, i.e. perfect interfaces model. The main impact of the imperfection on the results is a shift towards the low frequency of the equivalent parameter curves. Highlights: Development of an equivalent dynamic model for multilayered structures by taking into account imperfect interfaces. Impact of imperfect interfaces on equivalent parameters such as flexural rigidity or damping. Imperfect sliding interfaces modeled thanks to a spring-layer approach.